The Right of Intervention for the Protection of Nationals : Reassessing the Doctrinal Debate - Raby, Jean (Les Cahiers de droit, 1989)
The legality of a forceful intervention by a state to protect its nationals has been the subject of a continuing controversy over the past 15 years. Many see it as an unlawful use of force prohibited by the Charter of the United Nations, others see it as a lawful exercice of a self-standing right recognized under contemporary international law, some finally claim it falls under the scope of self-defence. The author proposes not to restate that debate, but more to reassess it, examining and challenging some of the arguments raised on both sides of the question. Within that debate, it will be concluded that the international legal order does indeed recognize the validity of the use of force for such a purpose : if the avenue of self-defence is rejected, for conceptual as well as practical reasons, the right of intervention to protect nationals is indeed, for the author, part of the comtemporary international legal order. Then, the author wishes to broaden the debate and proposes another option, which has not been explored by scholars and publicists but which is found more satisfactory than any other approach : intervention to protect nationals can be justified under international law because of the existence, in a particular case, of a "state of necessity" as defined by the International Law Commission.